The Strategic Role Of Brand Storytelling In Enhancing Marketing Management And Brand Awareness On Social Media Platforms - Wibowo, Sarwo Eddy; Aksenta, Almasari; Hartanto, Subhan (Jurnal Multidisiplin Sahombu, 2024)
In the digital age, social media is becoming an important platform for marketing, but a key challenge is how to differentiate brands in a saturated market. Brand storytelling emerges as a potential solution to build strong emotional connections with consumers and increase brand awareness. This research aims to explore the role of brand storytelling in increasing brand awareness on social media platforms through an explorative case study on MSME Kopi Nusantara. Qualitative methods were used with in-depth interviews, social media content analysis, participatory observation, and consumer surveys. The results showed that elements of authentic narrative, emotional engagement, consistency, and the use of strong visuals play an important role in the effectiveness of brand storytelling. Consumers respond positively to evocative and authentic stories, which increases brand awareness and loyalty. This study provides important insights for other MSMEs to adopt effective brand storytelling strategies on social media. Practical recommendations are provided to optimize key elements in brand narratives to achieve better marketing outcomes.